Effectiveness of interventions in preventing injuries in agriculture—a systematic review and meta-analysis - Lehtola, Marika M.; Rautiainen, Risto H.; Day, Lesley M.; Schonstein, Eva; Suutarinen, Juha; Salminen, Simo; Verbeek, Jos H. (Scandinavian Journal of Work, Environment & Health, 2008)
' ' OBJECTIVES ': 'This study reviewed the effectiveness of interventions in preventing occupational injuries among workers in agriculture. ' ' METHODS ': 'Randomized controlled trials, controlled before–after studies, and interrupted time-series studies assessing interventions aimed at preventing injuries among workers in agriculture were considered. MEDLINE and five other databases were searched up to June 2006. Two authors independently assessed the eligibility of studies and the methodological quality of the ones included. Randomized controlled trials were combined in a meta-analysis. Interrupted time-series studies were reanalyzed to assess the immediate and progressive effect on injuries. ' ' RESULTS ': 'Five randomized controlled trials and three interrupted time-series studies met the inclusion criteria. Six studies evaluated educational interventions and financial incentives, and two studies evaluated the effect of legislation. Three randomized controlled trials on educational interventions with 4670 adult participants did not indicate any injury-reducing effect, with a rate ratio of 1.02 (95% confidence interval 0.87–1.20), nor did two randomized controlled trials among children (6895 participants). Financial incentives decreased the injury level immediately after the intervention in one interrupted time-series study. Banning endosulfan pesticide in Sri Lanka led to a significant decrease in the trend of poisonings over time. Legislation requiring rollover protective structures on all tractors in Sweden did not produce a reduction in injuries, but the same requirement for new tractors was associated with a decrease in fatal injuries. ' ' CONCLUSIONS ': 'The reviewed studies provided no evidence that educational interventions are effective in decreasing injury rates among agricultural workers. Financial incentives may be a better means of reducing injury rates. Banning highly toxic pesticides may be effective. Legislation on safety devices on tractors yielded contradictory results.
Keywords: agriculture; data pooling; effectiveness; evaluation research; injury prevention; intervention; intervention study; meta-analysis; occupational accident; preventive measure; randomized controlled trial; review; systematic review